Household food insecurity associations with pregnancy hypertension, diabetes mellitus and infant birth anthropometric measures: a cross-sectional study of Iranian mothers - Elham Hojaji; Mobina Aghajani; Rosa Zavoshy; Mostafa Noroozi; Hassan Jahanihashemi; Neda Ezzeddin (Taylor & Francis Group, 2021)
Objective: The purpose of this study was to determine the associations between food insecurity on pregnancy and its outcomes. Materials and methods: This cross-sectional study was carried out on 700 Iranian mothers. Household socioeconomic status, prenatal information and household food security status were assessed using questionnaires. Data analysis was applied by SPSS version 22. Results: The results of the study showed a significant association between food insecurity with gestational diabetes mellitus. The results also showed a significant association between birth weight, and height with pregnancy-induced hypertension. Conclusion: food insecure women should be recognized, and receive appropriate training and assistance.